Relative Poverty and Inequality of Income Distribution in Indonesia Using Granger Causality Approach - Candra Mustika; Haryadi; Junaidi; Zamzami (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This research is a development of the theory of poverty, this study descriptively analyzes relative poverty and income distribution inequality and examines the causal relationship between relative poverty and income inequality in all provinces in Indonesia by using the Granger causality test analysis tool. Based on the results of the causality test, it shows that there is a unidirectional relationship between relative poverty and income distribution inequality, where it is the inequality of income distribution that causes relative poverty